INVESTIGATION ON HYBRID SOLAR-FLUE GAS CHIMNEY POWER PLANT - AJA, OGBOO CHIKERE (2013)
The mam purpose of solar chimney power plant is to generate electricity using primary renewable energy source and contribute in solving the growing global energy demand. Up to date, the solar chimney power plant has only been realized in small scale which is characterised of low plant efficiency where the Manzanares pilot plant of 45000 m2 collector area and 195 m chimney height operated at about 0.13% total efficiency. Solar chimney power plant efficiency is a product of the efficiencies of the plant components which are the open-solar air collector/greenhouse, the chimney and the turbine. The collector performance has been rated 30% and above depending on the type of collector material. Similarly, the turbine performance is in the range of 60% to 80% while the chimney performance is a function of its height. The performance of a I 000 m high-chimney is about 3.2% which make the total efficiency less than 2%. For the plant to be commercially viable, the plant needs to be more efficient and cost effective.